Composites Cu–Ti3SiC2 Obtained via Extrusion-Based Additive Manufacturing: Structure and Tribological Properties - Maksim Krinitcyn; Egor Ryumin; Georgy Kopytov; Olga Novitskaya (Metals)
In the present study, composites Cu–Ti3SiC2 were obtained via extrusion-based additive manufacturing technology. The composite was characterized in terms of its structure, mechanical properties, and tribological properties. The use of a low-energy additive manufacturing technique allows for the avoidance of the decomposition of the MAX phase while obtaining bulk samples. The optimal composition of 50 vol.% of Ti3SiC2 and 50 vol.% of Cu was selected based on the flow rate of feedstock melt and the density of the samples. The resulting composite exhibited a dense copper matrix with Ti3SiC2 and TiC inclusions, achieving 97% density and 62% IACS electrical conductivity. Tribological tests under varying loads, speeds, and temperatures demonstrated that increasing the load and speed increased the coefficient of friction and the wear rate, while higher temperatures reduced friction due to surface oxidation.